Genome Sequences of Three Microbacterium Phages Isolated from Flowers - Iles, Kerry S. (Microbiol Resour Announc, 2019)
Bacteriophages Balsa, Golden, and Lucky3 are cluster EA phages isolated from flowers and infect Microbacterium foliorum NRRL B-24224. The genomes of Golden and Lucky3 (subcluster EA1) are closely related, whereas Balsa (subcluster EA4) is a more distant relative.